Euastacus vesper sp. nov., a new giant spiny crayfish (Crustacea, Decapoda, Parastacidae) from the Great Dividing Range, New South Wales, Australia - Mccormack, Robert B.; Ahyong, Shane T. (Zootaxa, 2017)
Euastacus vesper sp. nov., is described from the upper Cudgegong River, Coricudgy State Forest, New South Wales, Australia. The new species occurs in the western drainage of the Great Dividing Range, and is most closely related to E. spinifer (Heller, 1865), which occurs on the eastern side of the range. Euastacus vesper differs from E. spinifer by its considerably smaller maximum size (OCL 67.9 mm versus 116.7 mm), greater degree of thoracic spination loosely arrayed in three instead of two rows and absence of the antennular basipodite and coxopodite spines. Observations on burrowing, ecological preferences and biology are presented.